2015
DOI: 10.1080/07055900.2015.1086970
|View full text |Cite
|
Sign up to set email alerts
|

Observed Trends in Severe Weather Conditions Based on Humidex, Wind Chill, and Heavy Rainfall Events in Canada for 1953–2012

Abstract: Observed trends in severe weather conditions based on public alert statements issued by Environment Canada are examined for Canada. Changes in extreme heat and extreme cold events represented by various humidex and wind chill indices are analyzed for 1953-2012 at 126 climatological stations. Changes in heavy rainfall events based on rainfall amounts provided by tipping bucket rainfall gauges are analyzed for 1960-2012 at 285 stations. The results show that extreme heat events, defined as days with at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Significant uncertainties and knowledge gaps remain, however. Model disagreements arise from uncertainty about greenhouse gas emissions, parameterization of physical processes (e.g., snow sublimation or Antarctic ice melt rates), and model structure variance (e.g., resolution, constants) (Hodson et al 2013;Mekis et al 2015). While models continue to improve, it is important to note why uncertainties arise and what the resulting ranges of climate projections mean for communities and policy makers.…”
Section: Uncertainty In Physical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant uncertainties and knowledge gaps remain, however. Model disagreements arise from uncertainty about greenhouse gas emissions, parameterization of physical processes (e.g., snow sublimation or Antarctic ice melt rates), and model structure variance (e.g., resolution, constants) (Hodson et al 2013;Mekis et al 2015). While models continue to improve, it is important to note why uncertainties arise and what the resulting ranges of climate projections mean for communities and policy makers.…”
Section: Uncertainty In Physical Modelsmentioning
confidence: 99%
“…While models continue to improve, it is important to note why uncertainties arise and what the resulting ranges of climate projections mean for communities and policy makers. Precipitation models continue to offer wide confidence intervals at regional levels, particularly when examining multi-variable conditions, such as blizzard conditions (snow-water equivalent, wind, and surface temperatures are all factors) (Mekis et al 2015). Sea level rise projections are complicated by uncertainty about the stability of the Antarctic ice sheet, with additional tens of centimeters of sea level rise possible (Deconto and Pollard 2016;James et al 2015;Mekis et al 2015).…”
Section: Uncertainty In Physical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal variations of regional heavy precipitation displayed strong inter-decadal variability with limited evidence of long-term trends over the latter part of the 20th century, except in the number of heavy snowfall events in fall and winter, which increased over all of northern Canada. Mekis et al (2015) found little evidence of changes in heavy rainfall events (accumulated rainfall > 10, 25, and 50 mm over periods of 1, 24, and 48 h, respectively) for the region over the period 1960-2012. They noted that there is no apparent regional pattern in such extreme events because they are highly localized and the station density is relatively low.…”
Section: Changes In Daily and Extreme Precipitationmentioning
confidence: 99%
“…Other indices showed mostly mixed, non-significant trends. Mekis et al (2015) examined trends in extreme heat and extreme cold events (days with at least one hourly humidex value above 30 and with at least one hourly wind chill value below −30, respectively) from 1953 to 2012 at 126 stations across Canada. They found that extreme heat events had increased significantly at many of the stations across Canada and extreme cold events had decreased significantly at virtually all stations.…”
Section: Changes In Daily and Extreme Air Temperaturesmentioning
confidence: 99%